Bioethics in the Times of Contagious Populism - Arguedas Ramírez, Gabriela (2021)
As I write this short piece, several social protests are happening in Costa Rica, where I live. The messages that protestors are sending out are very confusing, even contradictory. However, in the midst of this chaos, it’s still possible to identify certain emotions and narratives. There is plenty of frustration, fear, anger. The economic crisis exacerbated by COVID-19 has caused an increase in unemployment, which had already been growing rapidly during the last few years. Using conspiracy theories and false information about the SARS-Cov-2 virus, anti-democratic groups are taking advantage of the situation in an effort to destabilize the political and constitutional order.